Molecular symmetry breaking in the Frizzled-dependent planar polarity pathway. - Strutt, H.; Warrington, S.; Madathil, A.C.K.; Langenhan, T.; Strutt, D. (Current Biology, 2023)
The core planar polarity pathway consists of six proteins that form asymmetric intercellular complexes that segregate to opposite cell ends in developing tissues and specify polarized cell structures or behaviors. Within these complexes, the atypical cadherin Flamingo localizes on both sides of intercellular junctions, where it interacts homophilically in trans via its cadherin repeats, whereas the transmembrane proteins Frizzled and Strabismus localize to the opposite sides of apposing junctions. However, the molecular mechanisms underlying the formation of such asymmetric complexes are poorly understood. Using a novel tissue culture system, we determine the minimum requirements for asymmetric complex assembly in the absence of confounding feedback mechanisms. We show that complexes are intrinsically asymmetric and that an interaction of Frizzled and Flamingo in one cell with Flamingo in the neighboring cell is the key symmetry-breaking step. In contrast, Strabismus is unable to promote homophilic Flamingo trans binding and is only recruited into complexes once Frizzled has entered on the opposite side. This interaction with Strabismus requires intact intracellular loops of the seven-pass transmembrane domain of Flamingo. Once recruited, Strabismus stabilizes the intercellular complexes together with the three cytoplasmic core proteins. We propose a model whereby Flamingo exists in a closed conformation and binding of Frizzled in one cell results in a conformational change that allows its cadherin repeats to interact with a Flamingo molecule in the neighboring cell. Flamingo in the adjacent cell then undergoes a further change in the seven-pass transmembrane region that promotes the recruitment of Strabismus.